2020
DOI: 10.18510/hssr.2020.8167
|View full text |Cite
|
Sign up to set email alerts
|

Learning Vocabulary Through Songs: A Study on the Role of Music in Teaching Verbs

Abstract: Purpose of the study: This study aims to investigate how the use of songs in English language classrooms could aid tertiary students to increase their verb vocabulary repertoire. Methodology: This quantitative study was carried out among diploma students from a local university in Malaysia. The students were exposed to various English songs during their English lessons. Pre-test and post-test were conducted in this study. Main Findings: The use of songs can increase vocabulary acquisition among Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The result is in line with Wardiansyah et al (2019) that students who had a high rate of listening to English songs habitually achieved a high rate of vocabulary mastery. Besides, the findings of this study also supported by numerous researchers that the activity of listening to music and song elevates vocabulary exposure with a positive cognitive emotional vibe (Azmin Md Zamin et al, 2020;Sari, 2013;Savitri & Rahman, 2016;Vitasmoro & Jatmiko, 2018). Results of the participants' views showed that while listening to English pop songs, they felt entertained and joyful with learning vocabulary.…”
Section: The English Pop Songs Use In Augmenting the Students' Vocabu...supporting
confidence: 83%
See 1 more Smart Citation
“…The result is in line with Wardiansyah et al (2019) that students who had a high rate of listening to English songs habitually achieved a high rate of vocabulary mastery. Besides, the findings of this study also supported by numerous researchers that the activity of listening to music and song elevates vocabulary exposure with a positive cognitive emotional vibe (Azmin Md Zamin et al, 2020;Sari, 2013;Savitri & Rahman, 2016;Vitasmoro & Jatmiko, 2018). Results of the participants' views showed that while listening to English pop songs, they felt entertained and joyful with learning vocabulary.…”
Section: The English Pop Songs Use In Augmenting the Students' Vocabu...supporting
confidence: 83%
“…Gushendra (2017) and Listiyaningsih (2017) reported that applying music and song assists EFL learners in enriching assorted words. In addition, incorporating music and song in learning vocabulary offered an enjoyable (Savitri & Rahman, 2016), relaxed atmosphere (Vitasmoro & Jatmiko, 2018), participative (Azmin Md Zamin et al, 2020) and stress-free vocabulary learning (Sari, 2013). Nurkolip and Hanafi (2019) found that the intensity of listening to songs could elevate the student's vocabularies.…”
Section: Introductionmentioning
confidence: 99%
“…Noor Arina Nadiah Abdul Razak & Melor Md Yunus in their research discovered that using action song improve the learners vocabulary acquisition mainly in action words (Razak et al,2016). Supporting the research,another study was proven to increase vocabulary acquisition among English language learners at tertiary level with the use of songs is able to provide a fun way of picking up new words (Zamin et al, 2020). In addition,incorporating song is affordable,the educators are not require to be in a training to involve song in the teaching.Incorporating song in teaching of an in depth input such as the grammar is much encouraging as the song proven to ease the learning.…”
Section: B Sing Along Songmentioning
confidence: 86%
“…This means that the pharmacy learners invoke their emotions to motivate their learning by lowering anxiety using music. The use of songs has been identified in several studies (Mailawati & Anita, 2022;Murad et al, 2018;Zamin, et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly. Zamin et al (2020) investigated the use of songs in English language classrooms in increasing their vocabulary. The result indicated that songs can increase vocabulary acquisition among English language learners.…”
Section: Discussionmentioning
confidence: 99%